(untitled) (Al-Aasar, 2025)
If it is said that Naat has priority in the beginning of Islamic poetry, it is not wrong because Naat and Manqabat are at the forefront of the poetic genres that became popular and popular among Muslims after the advent of Islam. They are related to Islamic foundations, beliefs, truthfulness, sincerity, and love for the Prophet. If it is said that Naat has priority in the beginning of Islamic poetry, it is not wrong because Naat and Manqabat are at the forefront of the poetic genres that became popular and popular among Muslims after the advent of Islam. They are related to Islamic foundations, beliefs, truthfulness, sincerity, and love for the Prophet.